High prevalence of ventricular repolarization abnormalities in people carrying TGFβR2 mutations - F. Extramiana (Nature Portfolio, 2018)
Abstract Mutations in the TGFβR2 gene have been associated with a life threatening risk of aortic dissection but no arrhythmic death has been previously reported. Two young females carrying a TGFβR2 mutation, initially diagnosed as Marfan syndrome or Loeys Dietz syndrome, presented sudden death with autopsy ruling out dissection. The ECGs of the 2 Sudden Cardiac Deaths revealed profound ventricular repolarization abnormalities with a sinusoidal T-U morphology associated with normal left ventricular ejection fraction. These data strongly suggest sudden cardiac arrhythmic deaths and prompted us to systematically study the repolarization pattern in the patients with TGFβR2 mutations. ECG findings from 58 mutation carriers patients (TGFβR2 group) were compared with those of 46 non-affected first degree relatives (control group). TGFβR2 mutation was associated with ventricular repolarization abnormalities in 47% of patients (p < 0.001 vs. controls), including a 19.6 ms (95%CI 8.7; 30.5) QTc interval prolongation compared to the non-affected first degree relatives (p < 0.001), higher prevalence of abnormal U waves (16% vs. 2%), and sinusoidal T-U morphology (10% vs. 0%). TGFβR2 mutations can be associated with abnormal ventricular repolarization pattern, longer QT interval than non-carrier relatives and an increased risk for sudden death.